The Crisis Sensitivity of European Countries and Regions: Stylized Facts and Spatial Heterogeneity - Stefan P.T. Groot; Jan L. Mohlmann; Harry Garretsen; Henri L.F. de Groot (Tinbergen Institute, 2011)
This paper investigates the impact of the recent global recession on European countries and regions. We first present several stylized facts as to the heterogeneous impact of the global recession on individual European countries and regions. We then offer an investigation of three main classes of explanations for spatial heterogeneity in the severity of the crisis. The first is the extent to which countries are integrated in the global economy via financial and trade linkages. A second class of potential explanations is found in differences in the institutional framework of countries. A third possible cause why some countries and notably also regions are more affected than others is differences in their sectoral composition. We show that especially variation in the sectoral composition contributes to the variation in the effects of the current crisis, both at the country level and at the detailed regional level across the EU.
Keywords: E02; E32; E63; F44; O52; R11; 330; recession; austerity; Europe; spatial heterogeneity; Konjunktur; Haushaltskonsolidierung; Wirtschaftskrise; Wirtschaftliche Anpassung; Vergleich; EU-Staaten